Mario Molina and the saga of ozone example of linking science and society (Andamios, Revista de Investigación Social, 2015)
We present an analysis between research article published in 1974 which alerted the world about the loss of the ozone layer and in parallel on one of its authors, Mario Molina. We review how the study came about and which were its societal consequences out of the academic scientific ambit. Through this particular point of view we characterize the relationship science-society around three lines of analysis: infrastructure, leadership and flexibility. We use this characterization to ponder opportunities for Latin America like interaction between government, academy and industry, the investment in science and technology and long term projects.
Keywords: Science-society; ozone layer; infrastructure; leadership; flexibility